Late Pleistocene Lemmings (Lemmus trimucronatus and Dicrostonyx groenlandicus; Muridae: Rodentia) from Alberta, Canada - Burns, James A. (Journal of Mammalogy, 2004)
A gravel quarry near Edmonton, Alberta, Canada, yielded remains of micromammalian taxa not previously reported in the mid-Wisconsinan (late Pleistocene) interstadial “local fauna.” A left M1 and an upper incisor fragment of Lemmus trimucronatus and a left M2 of Dicrostonyx groenlandicus were recovered. These finds represent the 2nd Pleistocene record for Lemmus in Alberta, the 3rd for Dicrostonyx , and the 1st for both taxa from a northern Great Plains site. They help to fill distributional gaps between Beringia and the midcontinent. In association with those of large grazing megaherbivores, these new arvicoline finds support the inference of a cool, fairly dry steppe in central Alberta during the last interstadial.